Analysis of The Influence Of Menu Innovation on Consumer Satisfaction At Mcdonald's (Survey of Consumers Visiting Mcdonald's City of Bandung) - Hanifah, Nida; Siswhara, Gita; Fajri, Ilham (Gastronomy Tourism Journal, 2019)
This study aims to determine the effect of menu innovation on consumer satisfaction in McDonald’s City of Bandung. The method used in this research is a quantitative method by using a descriptive and verification approach. The sampling used refers to the results of the implementation of non-probability sampling techniques, namely by approaching consumers as many as 400 respondents who have visited McDonald's in Bandung and tried the innovation menu during the research period. The analysis technique used is a simple linear regression analysis, because in this study using two variables namely the menu innovation variable as the X variable and customer satisfaction as the Y variable. The results of the analysis that the authors get about the Innovation Menu on Consumer Satisfaction at McDonald's has a positive influence either partially or simultaneously with a magnitude of 77.1% on customer satisfaction. Seeing these results, then McDonald's has to do deepening, development, evaluation, and increasing customer satisfaction in making menu innovations so as to increase the value of customer satisfaction.